Use Pattern of Information Sources by Post-Graduate Students in a University Environment: A Case Study of Gulbarga University, Gulbarga - Tadasad, P. G.; Metesheela, D. (Journal of Information and Knowledge, 2001)
Based on the study of two hundred and four post-graduate students of Gulbarga University, the relative importance of information sources among the post-graduate students in a university environment is emphasised. The study reveals that books, newspapers, popular magazines, class notes, notes of seniors, are the most useful sources of information. General dictionaries, subject dictionaries, subject encyclopedia and scientific periodicals are also useful sources for the post-graduate students. Memoranda, diaries and letters, CD databases, trade catalogs, theses/dissertations, microforms, laboratory notes, handbooks, human sources, course materials of Open Universities, guide to subject literature, directories, statistical sources, biographical sources, library catalog, almanacs, manuals, geographical sources, research reports, are never used by a majority of post-graduate students. Based on statistical tests, the study concludes that the personal attributes viz., gender, year of study, medium of instruction at under-graduate and post graduate level, area of habitation, stay at hostels, marital status, and frequency of visits to University library have no bearing on the use of specific sources of information.